Mapping intracellular pH in tumors using amide and guanidyl CEST-MRI at 9.4 T - Boyd, Philip S.; Breitling, Johannes; Korzowski, Andreas; Zaiß, Moritz; Franke, Vanessa L.; Mueller-Decker, Karin; Glinka, Andrey; Ladd, Mark E.; Bachert, Peter; Goerke, Steffen (Magnetic Resonance in Medicine, 2021)
Purpose In principle, non-invasive mapping of the intracellular pH (pH(i)) in vivo is possible using endogenous chemical exchange saturation transfer (CEST)-MRI of the amide and guanidyl signals. However, the application for cancer imaging is still impeded, as current state-of-the-art approaches do not allow for simultaneous compensation of concomitant effects that vary within tumors. In this study, we present a novel method for absolute pH(i) mapping using endogenous CEST-MRI, which simultaneously compensates for concentration changes, superimposing CEST signals, magnetization transfer contrast, and spillover dilution. Theory and Methods Compensation of the concomitant effects was achieved by a ratiometric approach (i.e. the ratio of one CEST signal at different B-1) in combination with the relaxation-compensated inverse magnetization transfer ratio MTRRex and a separate first-order polynomial-Lorentzian fit of the amide and guanidyl signals at 9.4 T. Calibration of pH values was accomplished using in vivo-like model suspensions from porcine brain lysates. Applicability of the presented method in vivo was demonstrated in n = 19 tumor-bearing mice. Results In porcine brain lysates, measurement of pH was feasible over a broad range of physiologically relevant pH values of 6.2 to 8.0, while being independent of changes in concentration. A median pH(i) of approximately 7.2 was found in the lesions of 19 tumor-bearing mice. Conclusion The presented method enables non-invasive mapping of absolute pH(i) values in tumors using CEST-MRI, which was so far prevented by concomitant effects. Consequently, pre-clinical studies on pH(i) changes in tumors are possible allowing the assessment of pH(i) in vivo as a biomarker for cancer diagnosis or treatment monitoring.
CRIS-Team WoS Importer:2022-01-07